Desain Pembelajaran Penjumlahan dan Pengurangan Bilangan Bulat Menggunakan Matematika Realistik Konteks Permainanan Tradisional Congklak di SD Inpres Nunbaun Delha - Lantakay, Chindy Novelin; Samo, Damianus D.; Blegur, Irna Karlina Sensiana (Universitas Nusa Cendana, 2024)
This research aims to determine the learning design for adding and subtracting integers using realistic mathematics in the context of congklak (Indonesian Traditional Game ) at SD Inpres Nunbaun Delha. The method used in this research is design research, focused on developing learning designs in the form of hypothetical learning trajectories. This is a qualitative research involving 6 students in the pilot experiment cycle and 24 students in the teching experiment cycle. The data collection techniques used were tests, field notes, interviews and documentation. Meanwhile, data analysis techniques were carried out qualitatively. Thi sresearch produces a learning design using the PMRI approach. The resulting learning design consists of 7 activities where the PMRI approachis the main reference in each activity. The contextused in this researchis the traditional game congklak. Students were asked to play the traditional game congklak. After that, students observed the process of playing the traditional game congklak. Students were given congklak which had been modified to play. Then students solve the problems by playing congklak which has been modified in the way they play. Next, students draw circles to solve problems involving adding and subtracting integers. After that, students solve problems without using congklak or pictures of circles and end with students concluding the concept of adding and subtracting integers.